Mouse genetics identifies unique and overlapping functions of fibroblast growth factor receptors in keratinocytes. Issue 2 (12th December 2019) - Meyer, Michael; Ben‐Yehuda Greenwald, Maya; Rauschendorfer, Theresa; Sänger, Catharina; Jukic, Marko; Iizuka, Haruka; Kubo, Fumimasa; Chen, Lin; Ornitz, David M.; Werner, Sabine
Abstract: Fibroblast growth factors (FGFs) are key regulators of tissue development, homeostasis and repair, and abnormal FGF signalling is associated with various human diseases. In human and murine epidermis, FGF receptor 3 (FGFR3) activation causes benign skin tumours, but the consequences of FGFR3 deficiency in this tissue have not been determined. Here, we show that FGFR3 in keratinocytes is dispensable for mouse skin development, homeostasis and wound repair. However, the defect in the epidermal barrier and the resulting inflammatory skin disease that develops in mice lacking FGFR1 and FGFR2 in keratinocytes were further aggravated upon additional loss of FGFR3. This caused fibroblast activation and fibrosis in the FGFR1/FGFR2 double‐knockout mice and even more in mice lacking all three FGFRs, revealing functional redundancy of FGFR3 with FGFR1 and FGFR2 for maintaining the epidermal barrier. Taken together, our study demonstrates that FGFR1, FGFR2 and FGFR3 act together to maintain epidermal integrity and cutaneous homeostasis, with FGFR2 being the dominant receptor.